2010
DOI: 10.1071/bt09134
|View full text |Cite
|
Sign up to set email alerts
|

Ovule ontogeny of Relbunium species in the evolutionary context of Rubiaceae

Abstract: Carpel and ovule ontogeny, gynosporogenesis and gynogametogenesis in species of Relbunium were studied in order to provide additional data distinguishing evolutionary embryological characters. No significant differences in either ontogeny or morphology were observed among the species. The following characteristics are common to all species studied: (1) an independent development between the establishment of carpels and placenta meristem; (2) a bi-layered structure of the ovule primordia; and (3) a remnant gyno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Anatomical features, especially reproductive ones, have been used in recent studies to improve taxonomic delimitation in different groups, as they exhibit low phenotypic plasticity compared with vegetative characters (Taylor & Robinson, ; Palací, Brown & Tuthill, ; Sajo, Prychid & Rudall, ; De Toni & Mariath, ; Fagundes & Mariath, , ). Embryological features can provide >50 characters associated with the development of anthers, ovules and seeds, contributing to a better understanding of the relationships among families and genera (Tobe, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomical features, especially reproductive ones, have been used in recent studies to improve taxonomic delimitation in different groups, as they exhibit low phenotypic plasticity compared with vegetative characters (Taylor & Robinson, ; Palací, Brown & Tuthill, ; Sajo, Prychid & Rudall, ; De Toni & Mariath, ; Fagundes & Mariath, , ). Embryological features can provide >50 characters associated with the development of anthers, ovules and seeds, contributing to a better understanding of the relationships among families and genera (Tobe, ).…”
Section: Introductionmentioning
confidence: 99%
“…Embryological features can provide >50 characters associated with the development of anthers, ovules and seeds, contributing to a better understanding of the relationships among families and genera (Tobe, ). Studies such as the observations of ovule development have proved to be efficient in differentiating taxonomic groups, not only by confirming phylogenetic relationships but also by revealing evolutionary patterns within the groups (Tobe & Raven, ; Anton & Cocucci, ; Juncosa & Tobe, ; Tobe, ; Moço & Mariath, ; De Toni & Mariath, , ; Fagundes & Mariath, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the most recent studies, Figueiredo et al (2013a; proposed new embryological characters for analysis, such as placenta position and origin of the carpellary septa. These embryological analyses have corroborated molecular phylogenies of Rubiaceae (De Toni & Mariath 2010). …”
Section: Introductionmentioning
confidence: 64%
“…Maheshwari, 1950;Palser, 1975;Herr, 1984;Tobe, 1989;De Toni & Mariath, 2010). Some characters do not exhibit significant variations in the subfamily, such as ovule orientation, number of integuments, thickness of the parietal tissue and nucellar epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic value of ovule characters has long been noted, and authors have usually demonstrated the utility of embryological information in clarifying relationships among taxa (e.g. Maheshwari, 1950;Palser, 1975;Herr, 1984;Tobe, 1989;De Toni & Mariath, 2010).…”
Section: Discussionmentioning
confidence: 99%